The Moderating Effect of Perceived Online Privacy Risk on the Relationship between Merchant Characteristics and Willingness to Disclose Personal Data - Pimrabiab, Pathou; Bovornusvakool, Witsinee; Pornprasertmanit, Sunthud; Triukose, Sipat; Srinutapong, Supoet (Creative Business and Sustainability Journal, 2021)
The purpose of this research study is to explore the relationship between perceived online merchant characteristics and willingness to disclose personal data, while examining the moderating effect of perceived online privacy risk. An online survey was employed to collect data from 354 samples, which resulted in a total of 1,062 respondents. The results showed that the effect of perceived online merchant characteristics on the willingness to disclose personal data was significantly moderated by the level of perceived online privacy risk. In other words, ratings of online merchant characteristic interacted significantly with perceived online privacy risk which influenced participant’s willingness to disclose personal data. This positive interaction depended on the level of perceived online privacy risk. That is, individuals with a high level of online privacy risk were less willing to disclose their personal data, while those with a low level of online privacy risk were significantly more likely to disclose such information. The willingness to disclose personal data was high when perceived online merchant characteristic ratings were high in both low and high levels of perceived online privacy risk.